Construction and test of low cost X-ray tomography scanner for physical-chemical analysis and nondestructive inspections - De Oliveira Jr., José Martins; Martins, Antonio César Germano [UNESP] (AIP Publishing, 2009)
X-ray computed tomography (CT) refers to the cross-sectional imaging of an object measuring the transmitted radiation at different directions. In this work, we describe the development of a low cost micro-CT X-ray scanner that is being developed for nondestructive testing. This tomograph operates using a microfocus X-ray source and contains a silicon photodiode as detectors. The performance of the system, by its spatial resolution, has been estimated through its Modulation Transfer Function - MTF and the obtained value at 10% of MTF is 661 μm. It was built as a general purpose nondestructive testing device. © 2009 American Institute of Physics.
Keywords: Image analysis; Nondestructive inspections; Tomography; X-ray